Design and Development of Management Information Systems at the University of Lampung Library Repository Using the Laravel Framework. - Anwar Sahid; Gigih Forda Nama; Rio Ariestia Pradipta; Wahyu Eko Sulistiono; Qais Ali Al-Nuzaili (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
The University of Lampung has a library that is used to support the university's academic activities. One of the services at the Unila library is a digital library service that is used to upload scientific works into the repository, but there are still manual processes that are carried out repeatedly such as collecting requirements files, giving accounts and coordinating with students who require to come to the library continuously. so that the process carried out is not efficient. This study aims to build a management information system on the repository using the Laravel framework which can be used as a solution for the Unila library to make it easier for users to upload scientific works into the digital library repository. The development of this application uses the kanban method, which includes the process of analyzing system requirements, designing, developing to testing. The results of this study succeeded in providing a file upload service for account application requirements and uploading a repository link that was validated by the admin. The service is then tested using the blackbox method which produces the expected output so that it can be concluded that the application passes the test.